1991
DOI: 10.1080/00320719108711887
|View full text |Cite
|
Sign up to set email alerts
|

Geographic information systems within the national health service: the scope for implementation

Abstract: The paper starts by assessing some of the needs for information management within the health service in Great Britain. Geographic Information Systems are introduced, and some of the functions such as database management, networking and overlying are described. Principally, it is argued that GIS can fill the role as a health information system, resource management system, and has the potential to assist in family practitioner monitoring and epidemiological studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 3 publications
(2 reference statements)
0
13
0
Order By: Relevance
“…For clinics, this comparison demonstrated that shortest network time was also strongly correlated with shortest network path (Pearson correlation greater than 0.98) and good correlation was observed for Euclidean distance (Table 3). Unlike the previous results in North American cities (2,17), more accurate measures of distance (shortest network path and time distances) in 18.75% (6,8,13) 50.00% (1,5,6,8,12,13,15,16) Emam-Reza and Omeh-Leyla hospitals were considered as a single hospital because they are very close to each other. For hospitals information see Figure 1a and for clinics and GC location see Figure 2b .…”
Section: Minimum Distance Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…For clinics, this comparison demonstrated that shortest network time was also strongly correlated with shortest network path (Pearson correlation greater than 0.98) and good correlation was observed for Euclidean distance (Table 3). Unlike the previous results in North American cities (2,17), more accurate measures of distance (shortest network path and time distances) in 18.75% (6,8,13) 50.00% (1,5,6,8,12,13,15,16) Emam-Reza and Omeh-Leyla hospitals were considered as a single hospital because they are very close to each other. For hospitals information see Figure 1a and for clinics and GC location see Figure 2b .…”
Section: Minimum Distance Methodsmentioning
confidence: 89%
“…Geographical accessibility refers here to the ease with which patients of a given area can reach health services and facilities (3). Early applications of GIS in the health field focused on epidemiological issues (4)(5)(6) as the distribution and determinants of health and disease in groups (7). More recently increasing attention on GIS has been paid for public health management (8)(9)(10)(11) to examine geographical and spatial patterns of health services together with planning the location of new health facilities (12) and also in the spatial analysis of healthcare utilization (13).…”
Section: Introductionmentioning
confidence: 99%
“…For example, GIS can define the actual location of health events, and then overlay analysis can be used to create new spatial relationships and to tag the various socio-economic and environmental information to the health data. (Nicol, 1991).…”
Section: Spatial Epidemiologymentioning
confidence: 99%
“…Wirgley (1991), have also used GIS in mapping incidence of diseases in relation to population types. Another example of Geographic information systems application in epidemiology is called the Health and Environment Geographic information systems (HEGIS) which is being established in Europe by the World Health Organization (Nicol, 1991). It involves the creation of European wide environment data set, and the aim is to research relationship between health and the environment to aid policies and management.…”
Section: Spatial Epidemiologymentioning
confidence: 99%
“…More recently, geographical information systems (GISs) have been developed for health service use, and a wide range of possible functions was described by Nicol in 1991. 5 Examples of these applications have been published. 6 " 8 The purpose of this paper is to demonstrate how maps have been used in a health authority and associated Trusts, and to encourage others working in the health information field to use the relatively inexpensive and easy-to-use facilities now available to develop GISs of their own.…”
Section: Introductionmentioning
confidence: 99%